DISCURSIVE ANAPHORA PRAGMATIC MODELS IN MONOLOGIC TEXT - Galina Dmitrievna Sknar; Igor Alexandrovich Kudryashov (Russian Language Studies, 2017)
The aim of the article is to determine the pragmatic particularities of the monologist text thematic organization based on the discursive anaphora models. This aim predetermines the tasks connected with 1) outlining the conception of the theme as a textual segment manifesting sustained dependence on the fictional monologist text discursive scheme; 2) considering the fictional text monologist sphere based on the role the thematic components play in it; 3) revealing the referentially dependent anaphoric linguistic expression sequences which form the thematic components within the frameworks of the monologist text discursive scheme with regard to the communicative specifics of the text. The conclusions made in the article allow to get closer to a fuller understanding of how the cohesion relations and the anaphoric relations modeled by the thematic components facilitate the reader’s task on integrating the utterance discursive characteristics into a more global interpretative structure. It is proved that both phenomena forming the symbiosis realize the function of sustaining the meaning continuality and the referential plane of the connected utterances in the monologist text. This statement outlines the scientific significance of the research conducted. The practical significance of the article is determined by the possibility of using its basic results for further development of the problem of the «informational packing» for the utterances belonging to the monologist conversational genres, for revealing the mechanisms of the fictional text organization as the whole. The theoretic deductions achieved in the article could be used in teaching the contemporary Russian language in higher educational establishments, stylistics of decoding, special courses in philological hermeneutics and the courses devoted to the discursive basics of the monologist text organization.